Autoformação docente à luz do pensamento complexo - Arone, Mariangelica (2014)
This study examines the perspective of the construction of a teacher self-training, according to the conception of Edgar Morin s complex thought, supported by Gaston Pineau s tri-polar theory, by means of the interdependence of categories which are proper to the chosen theoretical reference, that intertwined and that helped to understand the possibility of a human training. The study starts from the premise that the knowledge of a theory, which is able to provide the basis of the interconnections of the complex net of relations and knowledges, which consider the human being in his multiple dimensions, can generate conceptions of the training processes. The purpose of this research is to show the perception of the role of self-training the people we interviewed have, more specifically to unveil and to understand how this proceeding occurs as a tool of their apprenticeship management. Field research was carried out by means of interviews conducted with eight teachers of two schools of basic education of the city of São Paulo. Thanks to the data gathering and to the analysis of the interviews, it was possible to identify the elaboration of means of self-training on the part of the protagonists, mainly in the facing of uncertainties, in the re-linking of scientific knowledge with humanitarian knowledge and in the reestablishment of the significant relationships and attitudes. The study revealed that self-training is the very creation of apprenticeship which is carried out by the teaching subjects in the course of their lives, in the sense of a better comprehension of the present actions, which are dependent on the relationship they have with themselves and their relationships with others, in constant movement and in a spiral of self-eco-organisation and in decision-making in order to manage their own knowledge.